Three-in-one is really better: exploring the sensing and adsorption properties in a newly designed metal–organic system incorporating a copper(ii) ion. Issue 34 (7th August 2019) - Khan, M. Shahnawaz; Khalid, Mohd; Ahmad, M. Shahwaz; Shahid, M.; Ahmad, Musheer
Abstract : A new Cu(ii ) material is designed as excellent sensor for nitrobenzene and ferric ions and a good adsorbent for organic dyes. Abstract : A 2-D copper(ii )-based coordination polymer, [Cu(SCN)(hmp)] n CP (1 ), was crystallized via the slow evaporation method after the reaction of CuSO4 ·5H2 O, 2-pyridinemethanol (hmpH), sodium thiocyanate and sodium hydroxide in water for functional applications. CP (1 ) was characterized via elemental analysis, FTIR, PXRD, magnetic, EPR, crystallographic and TGA studies. The crystal structure and EPR data confirmed a square pyramidal geometry around the Cu(ii ) ions. The topological analysis revealed that CP1 has a 6 ^ 3 point symbol with a [6.6.6] extended point symbol and 3-c net, uninodal net having hcb and Shubnikov hexagonal plane net/(6, 3) type of uncommon topology. The magnetic studies suggested the strong antiferromagnetic nature of CP (1 ). The fluorescence sensing property of CP (1 ) was investigated with different nitro aromatic compounds and hazardous metal ions. CP (1 ) demonstrated high selectivity and sensitivity towards nitrobenzene, even in the presence of other competitive nitro aromatics. In addition, CP (1 ) showed excellent selectivity and sensitivity toward Fe 3+ over other metal ions. The possible detection mechanisms were proposed employing UV-visible and fluorescence spectroscopy and DFT calculations. CP (1 ) also showed excellent recyclability towards both analytes, and its initial intensity was almost regained after several washings. Moreover, CP (1 ) acted as an excellent adsorbent material for natural dyes with different charges and sizes, i.e., methylene blue (MB), methyl orange (MO) and Rhodamine-B. Furthermore, CP (1 ) was utilized repeatedly for the effective adsorption of MB from wastewater without significant loss in its adsorption capacity. Hence, the present CP (1 ) was designed to relate coordination chemistry with various functional applications of interest.